Productividad forrajera de haba bajo diferentes condiciones de manejo - Estrada, Carmen Rosana (2017)
Faba bean forage productivity under different management conditions. Related to the production of Vicia faba L., beans and forage in Zaragoza, Puebla, different conditions of crop management were evaluated, such as soil preparation, fertilization and planting density. The experiment was conducted during the 2013 spring-summer crop cycle. Three variation factors were studied: 1) complete and minimum tillage; 2) compost application at 17.8 t.ha-1 and without compost; 3) planting 4, 6, 8 or 16 plants per m2. The experimental design was of randomized blocks, whith split plots and 4 replicates: large plots corresponded to 2 soil preparations, subplots to fertilization and small plots to 4 planting densities. The experimental units were plots of 3.0 x 5.6 m (16.8 m2), whose 6 central furrows were taken as the useful plot (8.4 m2). The largest production in biomass or total dry matter (10.15±1.9 t.ha-1) corresponded to treatments with complete preparation: 16 plants per m2 and application of compost (65 N; 0.54 P kg.ha-1). The dry matter production increased (p<0.05) as a function of the densities: 4, 6, 8 and 16 plants per m2, from 2.76±0.62 to 2.93±0.65.